Single-cell sequencing reveals the role of aggrephagy-related patterns in tumor microenvironment, prognosis and immunotherapy in endometrial cancer - Yuan, Yuquan; Ren, Chunyan; Shu, Jin; Zhu, Keyang; Li, Ganghui; Liu, Bao; Huang, Jianrong; Huang, Yinde; Zhao, Chengzhi (Frontiers in Oncology, 2025)
BackgroundAs a type of autophagy, aggrephagy degrades the aggregation of misfolded protein in cells and plays an important role in key genetic events for various cancers. However, aggrephagy functions within the tumor microenvironment (TME) in endometrial cancer (EC) remain to be elucidated.MethodsA total of 36,227 single cells from single-cell RNA-seq data derived from five EC tumor samples were comprehensively analyzed using a nonnegative matrix factorization (NMF) algorithm for 44 aggrephagy-related genes. Bulk RNA-seq cohorts from public repositories were utilized to assess the prognostic value of aggrephagy-related TME clusters and predict immune checkpoint blockade immunotherapeutic response in EC.ResultsFibroblasts, macrophages, CD8+T cells, and lymphatic endothelial cells were categorized into two to five aggrephagy-related subclusters, respectively. CellChat analysis showed that the aggrephagy-related subtypes of TME cells exhibited extensive interactions with tumor epithelial cells, particularly for macrophages. Moreover, aggrephagy regulators may be significantly associated with the pseudotime trajectories of major TME cell types as well as the clinical and biological features of EC. Bulk-seq analysis showed that these aggrephagy-related subclusters had significant predictive value for the survival and immune checkpoint blockade response in EC patients. Notably, immunohistochemical staining results manifested that the TUBA1A+ macrophage subtype was linked to less lymph node metastasis and longer survival, which were consistent with the bioinformatics analysis findings.ConclusionsThis study provided a novel view of aggrephagy signaling in the EC tumor microenvironment, and intervention of aggrephagy was expected to improve the survival rate of EC patients.